A review on the cytogenetics of the tribe Oryzomyini (Rodentia: Cricetidae: Sigmodontinae), with the description of new karyotypes - Moreira, Camila Do Nascimento [UNESP] (2020)
Oryzomyini represents the most diverse and speciose tribe of subfamily Sigmodontinae, with 29 genera and about 141 species. This great diversity of species is distributed from southeastern North to southern South America. Its systematics have passed through major changes in the last years due to the integration of molecular data with morphological characters in phylogenetic inferences. Unsurprisingly, cytogenetic studies on Oryzomyini reflect such diversity, with chromosome diploid number varying from 2n = 16 to 2n = 88. In addition, some species present autosomal and sex chromosome polymorphisms, besides the presence of B chromosomes. However, despite decades of cytogenetic studies, our knowledge about the karyotype variability in this group were still poorly known. Considering such deep and profound changes on the tribe, along with important new evidence that was continuously being produced associated to field work in several areas of Brazil and South America, we performed a cytogenetic review of the Oryzomyini group. We provide standardized descriptions summarizing all the knowledge associated to the known species of the tribe. We also describe seven new karyotypes for the tribe, Euryoryzomys sp., 2n = 58 and FN = 92; Neacomys sp. 1, 2n = 48 and FN = 54; Neacomys sp. 2, 2n = 54 and FN = 62; Oecomys sp. 1, 2n = 54 and FN = 84; Oecomys sp. 2, 2n = 64 and FN = 92; Oecomys sp. 3, 2n = 84 and FN = 110; and Scolomys sp., 2n = 62 and FN = 80.